Exploring variations in healthcare expenditures: What is the role of practice styles? - Alexander Ahammer; Thomas Schober (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2018)
Variations in the use of medical resources, both across and within geographical regions, have been widely documented. In this paper we explore physician practice styles as a possible determinant of these variations. In particular, we exploit patient mobility between physicians to identify practice styles among general practitioners (GPs) in Austria. We use a large administrative data set containing detailed information on a battery of different healthcare services, and implement a model with additive patient and GP fixed effects that allows flexibly for systematic differences in patients' health states. We find that, while GPs explain a relatively small part of the overall variation in medical expenses, heterogeneities in spending patterns among GPs are substantial. Conditional on patient characteristics, we document a difference of exteuro751.47 per patient per year in total medical expenses (which amounts to roughly 45% of the sample mean) between high- and low-spending GPs.
Keywords: I11; I12; C23; 330; Healthcare expenditures; practice styles; physician behavior; statistical decomposition